2017
DOI: 10.1155/2017/9832430
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin RegulatesIL-1βGene Expression in F4/80+ Macrophages during Synovial Inflammation

Abstract: Adrenomedullin (AM) plays an important role in the regulation of inflammatory processes; however, the role and expression of AM in synovial inflammation have not been determined. To investigate the expression and role of AM in inflamed synovial tissue (ST), the gene expression profiles of AM in the ST, including synovial macrophages and fibroblasts, of a murine patellar surgical dislocation model were characterized. In addition, the effects of interleukin- (IL-) 1β and AM in cultured synovial cells were also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Here, we found that ADM from H. pylori -infected gastric epithelial cells directly promoted T cell proliferation and IFN-γ production. Besides, we also found that ADM indirectly acted on T cells by IL-12 derived by ADM stimulated-macrophages, which resembles the data on IL-1β secretion in synovial inflammation [36]. It is clear that a mixed acute and chronic inflammatory reaction takes place in H. pylori -induced inflammatory environments, where multifarious immune cell types infiltrate and play complicated roles [37,38].…”
Section: Discussionsupporting
confidence: 74%
“…Here, we found that ADM from H. pylori -infected gastric epithelial cells directly promoted T cell proliferation and IFN-γ production. Besides, we also found that ADM indirectly acted on T cells by IL-12 derived by ADM stimulated-macrophages, which resembles the data on IL-1β secretion in synovial inflammation [36]. It is clear that a mixed acute and chronic inflammatory reaction takes place in H. pylori -induced inflammatory environments, where multifarious immune cell types infiltrate and play complicated roles [37,38].…”
Section: Discussionsupporting
confidence: 74%
“…NGF levels are elevated frequently in inflamed knee joints and have been linked to OA disease progression [15,22,23]. This is evidenced further by findings that NGF production is increased in synovial fibroblasts in the knees of OA patients [11].…”
Section: Discussionmentioning
confidence: 94%
“…Synovial macrophages produce inflammatory cytokines in response to synovial hyperplasia and under OA conditions [12,16,17,23]. Previous studies have also demonstrated an increased number of activated macrophages and IL-1b concentrations in the SYN of a synovial dysplasia mouse model [23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cxcl16 (a chemokine ligand), Cd248 (a transmembrane glycoprotein), Ptx3 (an in ammation induced gene), Fcrl2 (a subtype of Fc receptor-like molecules), Tgfb1i1 (a transforming growth factor beta 1 induced gene), Nostrin (a nitric oxide synthase tra c inducer), Vwf (an adhesive and multimeric glycoprotein), Tnxb (a member of the tenascin family), Ahr (a ligand-activated transcription factor), I t1 (an interferon-induced protein), Il2rb (an interleukin-2 receptor subunit) and Clec9a (a C-type lectin) are involved in the in ammation associated with arthritis pathology [71][72][73][74][75][76][77][78][79][80][81][82]. Ramp3 is a receptor activitymodifying protein that is highly expressed during joint in ammation [83]. Cyp1b1 (a member of the cytochrome P450 enzyme family), Pcsk1n (an inhibitor of prohormone convertase 1), Dlx3 (a family member of homeobox proteins), Nkd2 (a regulator of in ammatory response), Mmp19 (a subtype of matrix metalloproteinases), Htra4 (a subtype of serine proteases), Aplnr (a G protein-coupled receptor of apelin), Tubb2b (a beta isoform of tubulin), Arg1 (a cytosolic manganese-dependent enzyme) and Clic5 (a chloride intracellular channel protein) are reported to be highly expressed under osteoarthritic condition [84][85][86][87][88][89][90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%